Exploring gender differences in metacognitive reading strategy use among ESL university students during academic reading / Muhammad Nabil Mustafa - Mustafa, Muhammad Nabil (Faculty of Education, 2011)
This study explores the gender differences in metacognitive reading strategy use among ESL university students while reading academic texts of 200 Semester Two Diploma in Communication and Media Studies students, from the Faculty of Communication and Media Studies in UiTM Alor Gajah. Firstly, this study examines the metacognitive reading strategies used by male and female students in UiTM Alor Gajah while reading academic texts in terms of types and frequencies. Next, this study investigates the differences in the use of metacognitive reading strategies between male and female in term of type and frequencies. This research study is a non-experimental cross sectional survey design. The independent variable is the gender of the participants and the dependent variable is the metacognitive awareness as measured by Survey of Reading Strategies (SORS) developed by Mokhtari & Sheorey (2002) which is divided into three subscales which were global reading strategies (13 items), problem-solving strategies (8 items), and support strategies (9 items). Two research questions were examined using quantitative data analysis. The data for research questions were analyzed using descriptive statistics (Means and Standard Deviation) and inferential statistics namely one-way repeated measures (within subjects) ANOVA, Post-Hoc Bonferroni Adjusted Pairwise Comparison of Means test, and using independent samples t-tests. The findings reported that male and female students use problem-solving with high frequency while global and support strategies with moderate frequency. Male students used problem-solving strategies with the highest frequency followed by global strategies and support strategies while female students used problem-solving strategies with the highest frequency followed by both global strategies and support strategies. Female students used global and support strategies with similar frequency. Next, there was a significant difference in the frequency of use of support strategies between male and female students. Female students used support strategies with significantly higher than male students. Next, there were no significant differences in the frequency of use of problem-solving and global strategies between male and female students. Male and female students used problem-solving and support strategies with somewhat similar frequency. This study also discusses the pedagogical implications, limitations, and suggestions for future study.